Endoscopic repair of an injured internal carotid artery utilizing femoral endovascular closure devices. (29th January 2014) - Van Rompaey, Jason; Bowers, Greg; Radhakrishnan, Jay; Panizza, Benedict; Solares, C. Arturo
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Injury to the internal carotid artery is a feared complication of endoscopic endonasal surgery of the skull base. Such an event, although rare, is associated with high morbidity and mortality. Even if bleeding is controlled, permanent neurological defects frequently persist. Many techniques have been developed to manage internal carotid artery rupture with varying degrees of success. The purpose of this study was to explore endoscopic management of arterial damage with endovascular closure devices used for a femoral arteriotomy. The ability to remotely suture a damaged artery permits the possible adaptation of this technology in managing endoscopic arterial complications. Study Design Technical note. Methods After the creation of an endoscopic endonasal corridor in a cadaveric specimen, an arteriotomy was created at the cavernous portion of the internal carotid artery. The Angio‐Seal, StarClose, and MynxGrip vascular closure devices were utilized under endoscopic guidance to repair the arteriotomy. Angiography was then done on a cadaver sutured with the StarClose. Results Both the Angio‐Seal and StarClose were deployed quickly and appeared to provide sufficient closure of the arteriotomy. The Angio‐Seal required the use of a guidewire and was longer to deploy when compared with the StarClose. The StarClose deployment was quick and facile. The MynxGrip also deployed without difficulty. Conclusions The Angio‐Seal and StarClose systems were both successfully deployed utilizing an endoscopic endonasal approach. The MynxGrip was the easiest to deploy and has the greatest potential to be of benefit in this application. Further studies with hemodynamic models are required to properly assess the appropriateness in this setting. Level of Evidence NA Laryngoscope, 124:1318–1324, 2014